Implementation of P5 Entrepreneurship Theme in Forming Independent Character in Poboya State Elementary School - Sri Wahyuni; Ira Nuriya Santi; Zakiyah Zahara; Muhammad Riswandi Palawa4 (Journal of Humanities, Community Service, and Empowerment, 2024)
Strengthening character education is an important aspect of national education development, which aims to form the next generation of the nation with integrity and national insight. One of the real efforts in realizing this is through the implementation of Pancasila values in the school environment. This article discusses the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of entrepreneurship at SD Negeri Poboya as an example of good practice in shaping students' independent character. This research uses a descriptive qualitative approach to explore the implementation process, challenges, as well as the impact of the project on students' character. The results showed that P5 at SD Negeri Poboya was able to make a significant contribution in strengthening students' character, especially in terms of independence and responsibility. However, the successful implementation of this project can still be improved through stronger synergy between the school, parents and external partners. Program sustainability and joint commitment from all stakeholders are key factors in making P5 an inspiring character education model that can be replicated in other schools in Indonesia.